2018
DOI: 10.1002/jcsm.12351
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of early multimodal interventions for elderly patients with advanced pancreatic and non‐small‐cell lung cancer

Abstract: Background Combinations of exercise and nutritional interventions might improve the functional prognosis for cachectic cancer patients. However, high attrition and poor compliance with interventions limit their efficacy. We aimed to test the feasibility of the early induction of new multimodal interventions specific for elderly patients with advanced cancer Nutrition and Exercise Treatment for Advanced Cancer (NEXTAC) programme. Methods This was a multicentre prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 39 publications
3
145
0
Order By: Relevance
“…Because cancer cachexia is a syndrome caused by multiple factors, including loss of general activity because of fatigue and poor oral intake, if the study design had included improvement in muscle function as a co‐primary endpoint, then it should have included daily burden to muscle by rehabilitation and exercise. This comprehensive approach to investigating cancer cachexia syndrome is being carried out in Japan and internationally . It is hoped that the results will provide insights into the potential benefits of multimodal intervention for the management of cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Because cancer cachexia is a syndrome caused by multiple factors, including loss of general activity because of fatigue and poor oral intake, if the study design had included improvement in muscle function as a co‐primary endpoint, then it should have included daily burden to muscle by rehabilitation and exercise. This comprehensive approach to investigating cancer cachexia syndrome is being carried out in Japan and internationally . It is hoped that the results will provide insights into the potential benefits of multimodal intervention for the management of cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials investigating multimodal interventions including exercise and nutrition targeting cachexia in older adults with cancer are needed. Evaluation of an early multimodal intervention consisting of both an exercise intervention and nutrition sessions in older adults with advanced pancreatic cancer and non-small cell lung cancer has demonstrated feasibility and is currently accruing as a randomized phase II study [90]. Also, a recently completed randomized controlled trial of a cancer rehabilitation program in older adults with cancer showed promise for increasing activity expectations and self-efficacy, although it did not improve functional status [91].…”
Section: Interventions For Cachexia and Sarcopenia In Older Adultsmentioning
confidence: 99%
“…Despite intensified research in the field, no medical therapy has emerged for a wider clinical application to prevent or even reverse the development of cachexia and muscle wasting. The medical treatment of cachexia includes a dietary supplementation of proteins, vitamins, or minerals . Multiple attempts have been made to identify and validate treatment options to counteract the development of muscle wasting.…”
mentioning
confidence: 99%